Becoming Vaishnava in an ideal Vedic city - Fahy, John (WYSE series in social anthropology, 2019)
"Becoming Vaishnava in an Ideal Vedic City centers on a growing multinational community of ISKCON (International Society for Krishna Consciousness) devotees in Mayapur, West Bengal. While ISKCON's history is often presented in terms of an Indian guru 'transplanting' Indian spirituality to the West, this book focusses on the efforts to bring ISKCON back to India. Paying particular attention to devotees' failure to consistently live up to ISKCON's ideals, and the ongoing struggle to realize the utopian vision of an 'ideal Vedic city', this book argues that beyond a focus on virtue, the anthropology of ethics must account for how moral systems accommodate the problem of moral failure"--